ECONOMIC, POLITICAL, AND CULTURAL EXCLUSION IN TOURISM DEVELOPMENT: A CASE STUDY OF SAJEK VALLEY, CHITTAGONG HILL TRACTS (Journal of Event, Tourism and Hospitality Studies, 2025)
This study examines the dynamics of social exclusion within the rapidly expanding tourism sector of Sajek Valley, located in the Chittagong Hill Tracts (CHT) of Bangladesh - a region inhabited by indigenous communities and subject to post-conflict reconstruction. Development of tourism is a part of such reconstruction and peace-building efforts within the region, as well as empowering the indigenous community. However, in many cases the development of tourism lacks proper inclusivity, rather introducing exclusionary elements that hinder the sustainable peace-building and reconstruction efforts. Sajek Valley is not an exception in this case. The research focuses on three intersecting dimensions of exclusion: economic, political, and social, with a particular emphasis on the lived experiences of indigenous groups such as the Tripura and Lusai communities. This location was selected due to the expanding nature of the tourism industry here: while tourism has boomed in Sajek Valley, it has done so without adequately addressing the socio-political vulnerabilities of local populations, making it a critical site for examining exclusion within tourism development. Utilizing qualitative methods, including 20 key informant interviews, 4 in-depth interviews, and 2 focus group discussions, the study employs thematic analysis to interpret the data, allowing for in-depth exploration of recurring exclusionary patterns. Findings reveal political exclusion manifested through lack of involvement in tourism planning, forced displacement, and inadequate indigenous representation in local decision-making bodies. Relationship exclusion is evident in deteriorating inter-ethnic relations, exacerbated by unequal power dynamics and externally influenced favoritism. Economic and resource exclusion appears through severe environmental stress, including water scarcity and deforestation, disproportionately burdening indigenous residents. The study contributes to the literature by offering grounded, context-specific insights into how tourism-driven development can reproduce inequalities in a post-conflict regions like CHT, where tourism is promoted as a tool for peacebuilding. The study underscores the urgent need for inclusive, participatory tourism planning and holistic policies that protects the rights and well-being of local communities.